2003
DOI: 10.1016/s0921-4488(02)00292-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the nature of nitrogen supplementation on voluntary intake, rumen parameters and ruminal degradation of dry matter in sheep fed oat silage-based diets

Abstract: The effects of nature of nitrogen supplementation on silage DM intake (SDMI), total DM intake (TDMI), rumen parameters and ruminal degradation of DM of silage and wheat straw were studied using four adult Noire de Thibar rams. Silage was made from predominantly oats harvested at milk stage and ensiled without preservative. The silage was offered ad libitum as the sole diet (OS) or supplemented with 450 g DM of iso-nitrogen (25.6 g/kg DM) and iso-energy (0.8 Unité Fourragère Lait: UFL/kg DM) concentrate contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Plasma urea concentrations were higher for N supplemented diets, but plasma ammonia concentrations were comparable between the dietary treatments. When urea was supplemented to the basal diet, the postprandial plasma ammonia concentrations increased markedly because a large part of the ammonia produced from supplemental urea in the rumen was directly absorbed from the rumen (Sinclair et al 2000) and ammonia-N concentrations did not differ between with and without urea supplementation by 4 h after feeding (Mahouachi et al 2003). Protein degradability of soybean meal in the rumen was greater and availability of amino acids for absorption was less than corn gluten meal, wet brewers' grains and distillers' dried grains with solubles in lactating cattle (Santos et al 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma urea concentrations were higher for N supplemented diets, but plasma ammonia concentrations were comparable between the dietary treatments. When urea was supplemented to the basal diet, the postprandial plasma ammonia concentrations increased markedly because a large part of the ammonia produced from supplemental urea in the rumen was directly absorbed from the rumen (Sinclair et al 2000) and ammonia-N concentrations did not differ between with and without urea supplementation by 4 h after feeding (Mahouachi et al 2003). Protein degradability of soybean meal in the rumen was greater and availability of amino acids for absorption was less than corn gluten meal, wet brewers' grains and distillers' dried grains with solubles in lactating cattle (Santos et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, soybean meal, one of the most important dietary protein sources, is costly, largely degraded in the rumen and less absorbed than other protein sources in lactating dairy cattle (Santos et al 1984). Urea, a non-protein N, is available at a low cost (Mahouachi et al 2003). Urea supplementation is widely applied and has benefits for the production of cows (Tedeschi et al 2002;Zinn et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The ammonia concentration in rumen fluid remained within the normal range in ewes and the values required for maximum fermentation and optimal microbial protein synthesis (8.5 to 30 mg (100 mL) −1 of rumen fluid) (McDonald et al, 2002). The peak of the concentration of NH 3 -N in the rumen at 2 h post feeding suggested that the protein sources in the rumen were degraded quickly, in the first 2 h (Mahouachi et al, 2003).…”
Section: Rumen Fermentationmentioning
confidence: 99%
“…Seppälä, Heikkilä, Mäki, and Rinne (2016) stressed that the purpose of using additives during ensiling is to inhibit the growth of undesirable micro-organisms so as to prevent spoilage of the feed, thereby minimizing energy and nutrient losses. The use of chemical additives in the ensiling of tropical forages has been tested for over two decades (Felix & Funso, 1994;Mahouachi, Haddad, Kayouli, Théwis, & Beckers, 2003;Miron, Kabala, Tockb, & Ben-Ghedalia, 1995), and the improvement and efficiency of production of preserved roughages (Nkosi et al, 2016;Roth et al, 2016) have been gradually contributing to animal production. Romão et al (2013), Chizzotti et al (2015) and Martins et al (2015) investigated and described the use of urea and calcium oxide as alkalinizing chemical additives in the ensiling of sugarcane.…”
mentioning
confidence: 99%